The temperature coefficient of the potential of zero charge of Ag single crystal face electrodes in aqueous electrolyte solution - Doubova, L.M.; Trasatti, S. (Condensed Matter Physics, 2001)
The temperature coefficient of the potential of zero charge of Ag single
crystal electrodes, dEσ₌₀/dT , was measured by recording capacitance
curves at different temperatures. Two experimental approaches
were adopted: the “continuity” and the “discontinuity” method, consisting
in recording curves at different temperatures without and with extraction
of the electrode from the solution, respectively. Appreciable differences
have been observed. The origin of the differences and their significance
are discussed in terms of keeping the appropriate conditions for the electrode/solution
interface during the experiments. На основі даних для ємності при різних температурах отримано температурний коефіцієнт потенціалу нульового заряду срібних моно-кристалічних електродів. Застосовано два типи експериментів: метод “неперервності” і “розривності”, що полягає в записі кривих ємності при різних температурах без і з виділенням вкладу електрода
в розчині відповідно. Виявлена суттєва різниця в результатах, походження і важливість якої досліджується при відповідних умовах експериментів для поверхні розділу електрод-розчин.